2018
DOI: 10.15226/2374-6890/5/6/001121
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers Through The Development, Progression and Chronic Complications of Diabetes Mellitus: A Mini-Review

Abstract: Biomarkers are widely known to be elevated in patients with obesity, diabetes and related chronic complications such as nephropathy, retinopathy and cardiovascular disease. Obesity epidemic has resulted in an increased risk of diabetes development and consequent cardiovascular mortality, leading to probing the usefulness of the inflammatory biomarkers triggered by adipose tissue in individuals at risk. However, current knowledge regarding the clinical usefulness of inflammatory markers in individuals progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…T2DM is predominantly due to the failure of the bodily tissues to respond to insulin or synthesize enough insulin [4,5]. Several scientific studies have indicated that diabetes affects the human quality of life by causing major risk factors for adverse complications such as stroke, amputation, kidney failure, and blindness, leading to significant morbidity and premature mortality [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…T2DM is predominantly due to the failure of the bodily tissues to respond to insulin or synthesize enough insulin [4,5]. Several scientific studies have indicated that diabetes affects the human quality of life by causing major risk factors for adverse complications such as stroke, amputation, kidney failure, and blindness, leading to significant morbidity and premature mortality [6][7][8].…”
Section: Introductionmentioning
confidence: 99%